Petnajst let delovanja knjižnice na Glasbeni šoli Jesenice - Jamar, Nina (Šolska knjižnica, 2018)
The article illustrates the Music School Jesenice school library operations. The occasion of its fifteenth anniversary is a time to reminisce about its past activities and look into future. Future focus should be on the best possible cooperation between the library and the students and teachers of the Music School Jesenice, and all efforts should be directed towards quality management and organization of the Music School Jesenice library.
Keywords: Glasbena šola Jesenice; glasbene šole; music libraries; Music School Jesenice; osnovne šole; primary schools; school libraries; šolske knjižnice